If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (12 + -1x)(x + 1)(x + -1) = 160 Reorder the terms: (12 + -1x)(1 + x)(x + -1) = 160 Reorder the terms: (12 + -1x)(1 + x)(-1 + x) = 160 Multiply (12 + -1x) * (1 + x) (12(1 + x) + -1x * (1 + x))(-1 + x) = 160 ((1 * 12 + x * 12) + -1x * (1 + x))(-1 + x) = 160 ((12 + 12x) + -1x * (1 + x))(-1 + x) = 160 (12 + 12x + (1 * -1x + x * -1x))(-1 + x) = 160 (12 + 12x + (-1x + -1x2))(-1 + x) = 160 Combine like terms: 12x + -1x = 11x (12 + 11x + -1x2)(-1 + x) = 160 Multiply (12 + 11x + -1x2) * (-1 + x) (12(-1 + x) + 11x * (-1 + x) + -1x2 * (-1 + x)) = 160 ((-1 * 12 + x * 12) + 11x * (-1 + x) + -1x2 * (-1 + x)) = 160 ((-12 + 12x) + 11x * (-1 + x) + -1x2 * (-1 + x)) = 160 (-12 + 12x + (-1 * 11x + x * 11x) + -1x2 * (-1 + x)) = 160 (-12 + 12x + (-11x + 11x2) + -1x2 * (-1 + x)) = 160 (-12 + 12x + -11x + 11x2 + (-1 * -1x2 + x * -1x2)) = 160 (-12 + 12x + -11x + 11x2 + (1x2 + -1x3)) = 160 Combine like terms: 12x + -11x = 1x (-12 + 1x + 11x2 + 1x2 + -1x3) = 160 Combine like terms: 11x2 + 1x2 = 12x2 (-12 + 1x + 12x2 + -1x3) = 160 Solving -12 + 1x + 12x2 + -1x3 = 160 Solving for variable 'x'. Reorder the terms: -12 + -160 + 1x + 12x2 + -1x3 = 160 + -160 Combine like terms: -12 + -160 = -172 -172 + 1x + 12x2 + -1x3 = 160 + -160 Combine like terms: 160 + -160 = 0 -172 + 1x + 12x2 + -1x3 = 0 The solution to this equation could not be determined.
| in(x)+in(2-x)=0 | | b/8-6=10 | | 7x-5=10+2x | | (100-10)*c=45 | | 5(8x-6)=34 | | y^2+100=0 | | -2(9x-7)+12=8 | | a/2+5=11 | | 100-10*c=100 | | 10+x=32-4 | | 3a+8b+7a-b= | | 15x-8-10x+6=53 | | 6g=17 | | 7x+4(3-5x)=0 | | 4m+7=51 | | 18y*18y-18y-16y*16y+12y-15= | | Y=2x128/52 | | 2(3x-4)=3x+25 | | 5x+13=-5(2+2x)-8x | | -50.5+-96.8-1.6y+24.2+y=190 | | eln(2x-3)=1 | | 5+x-3=3x | | Y=2x4-128/152 | | 12c-7-3c+9= | | 6x^2-36x-96=0 | | 8z+6z= | | 2ln(2x-3)=2 | | 32=-16t+56t | | x^2+y^2+12x+4y+36=0 | | 2s+7s= | | 21y+7y= | | 2x+x+10=55 |